2001
DOI: 10.1177/039139880102400608
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Recombinant Human Erythropoietin Therapy on Plasma Endothelin-1 Levels during Hemodialysis

Abstract: The correction of anemia with human recombinant erythropoietin (rHuEPO) in end stage renal disease is associated with hypertension in about one third of hemodialysis patients. The pathogenesis of the rHuEPO-induced hypertension is still uncertain, though evidence of the involvement of endothelial cells has emerged. The aim of this study was to determine plasma endothelin-1 during hemodialysis and to compare the endothelin-1 levels in hemodialysis patients with and without rHuEPO substitution. Nineteen stable p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
1
14
1
Order By: Relevance
“…The level of ET-1 is signifi cantly higher in the patients treated with hemodialysis when compared with the control group. Unlike previous studies, 8,15 we noticed a signifi cant decrease of the level of ET-1 and NO after dialysis compared to the values before dialysis, which we attribute to the characteristics of our group. A similar result was discovered in the patients treated with hemodialysis in the subgroup of the patients with stable values of pressure during the research of Raj et al 9 Unlike previous studies, 10,15 we did not fi nd signifi cant correlation between the weekly dosage of erythropoietin and the serum levels of ET-1 and NO, neither before, nor after treatment with dialysis.…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations
“…The level of ET-1 is signifi cantly higher in the patients treated with hemodialysis when compared with the control group. Unlike previous studies, 8,15 we noticed a signifi cant decrease of the level of ET-1 and NO after dialysis compared to the values before dialysis, which we attribute to the characteristics of our group. A similar result was discovered in the patients treated with hemodialysis in the subgroup of the patients with stable values of pressure during the research of Raj et al 9 Unlike previous studies, 10,15 we did not fi nd signifi cant correlation between the weekly dosage of erythropoietin and the serum levels of ET-1 and NO, neither before, nor after treatment with dialysis.…”
Section: Discussioncontrasting
confidence: 96%
“…However, the increased levels of ET-1 were not followed by an increase of blood pressure. 15 Takahasi et al showed that the level of ET-1 in plasma in hemodialysis patients grew only in patients whose intradialytic pressure increased by 10 mmHg after 8 weeks of using rhEPO. 11 Studies with patients with intradialytic hypertension show a signifi cant increase of ET-1 during dialysis and a signifi cant decrease of the ET-1/NO ratio at the end of dialysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have found that Epo-induced hypertension in hemodialyzed patients was associated with significantly increased circulating ET-1 concentrations (75)(76)(77) and that the accentuated ET-1 response to Epo was particularly great in the patients who exhibited the highest pressure response to Epo (74). In contrast to angiotensin II and norepinephrine, however, no ET-1 hypersensitivity was found, as evidenced by the similar changes in forearm resistance in response to ET-1 infusions with and without Epo (70).…”
Section: Role Of Enhanced Noradrenergic and Angiotensin II Sensitivitmentioning
confidence: 99%